Learning Problems as Predictors of Depressive Symptomology in Women TANF Recipients. - Wahler, Elizabeth A.; Otis, Melanie D.; Leukefeld, Carl G. (Journal of Poverty)
Little is known about relationships between barriers to self-sufficiency in the Temporary Assistance for Needy Families (TANF) population. This study utilized ordinary least squares regression to analyze secondary data from a nonprobability sample of 2,156 women TANF recipients to examine learning problems as a predictor of depressive symptomology. After controlling for substance abuse, intimate partner violence victimization, physical health problems, demographics, and difficulty with interpersonal relationships, learning problems significantly predicted depressive symptomology. Findings suggest that many TANF recipients with learning problems are at an increased risk of experiencing depressive symptomology. To assist these individuals with overcoming mental health issues, underlying causes should be identified and addressed.